1999
DOI: 10.1017/s0025727300065406
|View full text |Cite
|
Sign up to set email alerts
|

Shaping the medical market: on the construction of quackery and folk medicine in Dutch historiography

Abstract: It has been stated many times: traditionally, medical history was written by, for and about doctors, telling the story of unilinear scientific progress. Positivism tended to look at the history of medicine as a process of linear progress from religion through metaphysics to science, in which mankind was liberated from superstition and irrationality. This view was confirmed by the Weberian notion of a "disenchantment" of the world: in the course of the last few centuries, the influence of magic and animism was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…Health care has been compared to a "medical market," where all practitioners "bid" for the trust of their patients. 2 This establishes an ethos attack that sets up modern medicine as a conniving profit center, with the friendlier, seemingly straightforward, natural approach of alternative medicine standing in stark contrast. 2…”
Section: The Modern Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Health care has been compared to a "medical market," where all practitioners "bid" for the trust of their patients. 2 This establishes an ethos attack that sets up modern medicine as a conniving profit center, with the friendlier, seemingly straightforward, natural approach of alternative medicine standing in stark contrast. 2…”
Section: The Modern Approachmentioning
confidence: 99%
“…22 This stems in part from the historical shift from looking at the history of medicine as a linear progression of accumulating knowledge, with illness as an ontological unit and the physician as an educator, toward illness being determined by multiple factors: social, economic, political, and religious. 2 The traditional medical view sets up a patriarchal and hierarchal system where the patient is passive and reliant upon the doctor for treatment to the point of "addiction" to their dictates. 22 Alternative rhetoric argues that this reliance on orders creates a natural tension, like Eve being told not to eat the "apple" in the garden, and ultimately modern doctors "'hex' the healing process because of their incredulity in the human body's capacity to maintain wellness."…”
Section: Doctors As Deitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Mais recentemente, uma pesquisa na base de dados PubMed revelou artigos que denunciam essas fraudes há mais de meio século (27). Em 1993, quando a Internet ainda era mal conhecida fora dos meios acadêmicos, o conselho holandês de saúde divulgou um relatório sobre o uso de métodos de cura alternativos (26), concluindo que, mesmo ao final do século XX, a "cura pela fé" envolvia um crescente mercado de ilusões, tanto em número de consumidores como em variedade de produtos.…”
Section: Características Da Fraude E Vigilantes Do Comércio Fraudulentounclassified
“…Furthermore, as the advertisement above suggests, not only 'professional' physicians made use of a medical discourse to bolster their credibility. 4 In fact, studies have shown that experts of all kinds, ranging from academics to natural healers, mothers or priests, were dependent on their audiences for recognition of their authority. 5 To sum up, static divides -between the scientific and the popular sphere, between the expert and the lay public, and between orthodox and heterodox medicine -were nuanced by a more multifaceted interpretation of knowledge production, ascribing a more active role to historical actors outside of the academic world.…”
mentioning
confidence: 99%